A high‐throughput UHPLC MS/MS method for evaluation of tartaric and malic acid concentration in individual grapevine berries. (22nd September 2015) - Higginson, E.G.; Lloyd, N.D.R.; Kravchuk, O.; Ford, C.M.; Thomas, M.R.
Abstract: Background and Aims: The chemical composition of grape berries during development exhibits large variation within a single bunch. To monitor the change in the concentration of tartaric acid and malic acid between individual berries, a high‐throughput method using UHPLC‐MS/MS was developed to quantify these acids in berry extracts. Methods and Results: The results from analysis of single‐vine datasets indicated that there was a large variation in the concentration of tartaric acid and malic acid between individual berries and also between bunches of berries across a vine. From these data, an optimum sampling size of 30 berries per vine was determined, which has an estimated standard error under 10% of the expected average berry acid concentration. Conclusions: A high‐throughput UHPLC‐MS/MS method using the stable isotope dilution analysis has been developed to quantify tartaric acid and malic acid in individual berry extracts and extracts prepared from samples of multiple berries. Significance of the Study: This method enabled the study of variation in acid concentration and content between individual berries. This makes it possible to quantify the variation in the acids at several levels (berries, bunches and plants) and to recommend ideal sampling sizes for data collection in vineyards.